Radiative corrections to the forward-backward asymmetry in e + e − → π + π − - Gilberto Colangelo; Martin Hoferichter; Joachim Monnard; Jacobo Ruiz de Elvira (Journal of High Energy Physics, 2022)
Abstract We present a calculation of the C-odd radiative corrections to e + e − → π + π − in a dispersive formalism, concentrating on the leading pion-pole contribution in the virtual box diagrams. In particular, we show how the effect of a general pion vector form factor in the loop integral can be incorporated in a model-independent way and how the cancellation of infrared singularities proceeds in this case. The numerical results, dominated by the infrared enhanced contributions, indicate significant corrections beyond scalar QED, essentially confirming recent findings in generalized vector-meson-dominance models.